Diagnostic Test Method RT-PCR (GENEXPERT) in the Examination of Mycobacterium Tuberculosis - Rafista Deviyanti (Journal of Sustainability Science and Technology, 2022)
The ability of a test to correctly (accurately) identify those who are ill and those who are not is known as diagnostic testing. Diagnostic tests are used to rate RT-PCR effectiveness (gen expert). Laboratory examination procedures are validated using diagnostic tests. By determining the values of sensitivity, specificity, positive predictive test, and negative predictive test, this study aims to determine the diagnostic usefulness of the RT-PCR instrument (gen expert). This study used an analytical approach and a comparative study methodology (comparative study), comparing the outcomes of an analysis using the gold standard technique, namely the microscopic and RT-PCR techniques (GeneXpert). To assess the data's sensitivity, specificity, positive predictive test, and negative predictive test values, a 2x2 table tubulation computation was used. The RT-PCR approach has an 85.3 percent sensitivity, a 100 percent specificity, a 100 percent positive predictive value, and a 92.3 percent negative predictive value. The study's findings indicate that the RT-PCR method (gen expert) has an 85.3 percent sensitivity value, a 100 percent specificity, a 100 percent positive predictive value, and a 92.3 percent negative predictive value.